Persepsi Petani Terhadap Teknologi Revolusi Industri 4.0 Pada Usahatani Padi Sawah Di Desa Tompasobaru Dua Kecamatan Tompasobaru Kabupaten Minahasa Selatan - Sambuaga, Aditya Imanuel; Kumaat, Ribka Magdalena; Waney, Nordy F.L. (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the perception of lowland rice farmers towards technology 4.0 in lowland rice farming in Tompasobaru Dua Village, Tompasobaru District, South Minahasa Regency. Perception indicators of understanding, acceptance, mastery, application and prospects using a Likert scale. This research was conducted from June to July 2022. The data collected in this study is the perception data of rice farmers after participating in the socialization of industrial technology 4.0 in lowland rice farming. Sampling was done by means of purposive sampling as many as 30 samples. The results showed that the perception of lowland rice farmers to technology 4.0 in lowland rice farming was in the good category (perception index 77.66%). This means that rice farmers have a good understanding, acceptance, and mastery of the technology of the industrial revolution 4.0 so that they are expected to be able to apply 4.0 technology independently.